Mercury absorbent mixture. - Selamat, Jinap; Hajeb, Parvaneh; Abu Bakar, Fatimah; Bakar, Jamilah (2010)

(untitled)
This invention relates generally to a mercury removal mixture in seafoods, wherein the mixture containing a solution containing mercury absorbent agents. The present invention also relates to a method for producing the mixture, which is capable to reduce heavy metals such as mercury in fish flesh.